KONFLIK TOKOH UTAMA DALAM NOVEL KADO TERBAIK KARYA J.S. KHAIREN - Mien Ismy Sidratul Ayath; Aris Badara; Sri Suryana Dinar (PT. CASA CENDEKIA MEDIA, 2024)
The objective of this research is to describe the forms of conflicts experienced by the main character in the novel Kado Terbaik by J.S. Khairen. The method used in this research is qualitative descriptive method. Based on the research results on the novel Kado Terbaik by J.S. Khairen, the following conclusions can be drawn: The main character in the novel Kado Terbaik by J.S. Khairen is Rizki. The problems in the novel begin when Rizki and his two younger sisters are abandoned by their mother in an orphanage, but it is not a legitimate orphanage. Instead, it is an illegal orphanage involved in child exploitation and organ trafficking. The conflicts experienced by the main character in the novel Kado Terbaik by J.S. Khairen include external conflicts (physical conflicts and inner conflicts) and internal conflicts (inner conflicts). Physical conflicts involve tension between the main character and other characters, including physical fights and violence, while social conflicts include arguments or quarrels. Internal conflicts involve inner turmoil such as despair, confusion, disappointment, regret, restlessness, anxiety, longing, unfulfilled hopes, affection, fear, heartache, dilemma, compulsion, and sympathy.